'Fat, four‐eyed and female' 30 years later: A replication of Harris, Harris, and Bochner's (1982) early study of obesity stereotypes. (12th April 2016) - Grant, Sharon L.; Mizzi, Toby; Anglim, Jeromy
Abstract: Objective: This study aimed to replicate Harris, Harris, and Bochner's (1982) early experiment on obesity stereotyping to examine whether negative obesity stereotypes persist and in what form. Method: A sample of psychology students ( N = 506) read a description of a target described as female or male, overweight or average weight, and wearing glasses or not, who they subsequently rated on 12 descriptors. Results: Overweight targets were rated as significantly less active, assertive, athletic, attractive, happy, hardworking, masculine, popular, and successful than average weight targets. This negative stereotype effect of target weight was much larger than effects observed for sex or wearing glasses. There were no differences in effect sizes for target weight between this study and the original study. Conclusions: It was concluded that the negative obesity stereotypes reported by Harris et al. have persisted over a 30‐year period, despite the fact that people who are overweight are no longer a minority. Efforts are needed to challenge negative stereotyping of this group. Future research could examine why stereotypes of overweight people are resistant to change.